Forecasting technical manpower needs in agriculture in Kerala - Suja S L (Department of Agricultural Extension, College of Agriculture, 2004)
The study entitled "Forecasting technical manpower needs in agriculture in Kerala" was undertaken to forecast the technical manpower demand and supply in agriculture for a decade in Kerala. It was also aimed to study the characteristics of the existing employment pattern of technical manpower. Its aim also included to identify the constraints faced by the technical manpower in getting gainful employment in agriculture. The study was conducted in identified organizations in Kerala state. A sample of 150 agriculture graduates who were working in different sectors of agricultural development in the state were selected for studying the characteristics of existing employment pattern in the state. The study developed after having discussion with the officials and subject matter specialists. Well structured and pre-tested interview schedule was used for data collection. For forecasting the technical manpower demand in the next decade, data regarding the employment pattern during the last five years and at present were collected from the government sector, industrial and corporate sector, research and academic sector, banking sector, non- governmental organizations and others. Then the trend of variation in the employment pattern was analysed. Based on this trend future technical manpower requirement in different sectors was worked out by regression analysis, For technical manpower supply forecasting agricultural students enrolled in Kerala Agricultural University from 1995 - 2002 were collected. In this study based on the data it \\';\'S assumed that 25 per cent of the students were coming from outside Kerala. The study revealed that most of the respondents were working in identified organizations whose functional area IS' research and